Dicer functions as an antiviral system against human adenoviruses via cleavage of adenovirus-encoded noncoding RNA - Machitani, Mitsuhiro (Sci Rep, 2016)
In various organisms, including nematodes and plants, RNA interference (RNAi) is a defense system against virus infection; however, it is unclear whether RNAi functions as an antivirus system in mammalian cells. Rather, a number of DNA viruses, including herpesviruses, utilize post-transcriptional silencing systems for their survival. Here we show that Dicer efficiently suppresses the replication of adenovirus (Ad) via cleavage of Ad-encoding small RNAs (VA-RNAs), which efficiently promote Ad replication via the inhibition of eIF2α phosphorylation, to viral microRNAs (mivaRNAs). The Dicer knockdown significantly increases the copy numbers of VA-RNAs, leading to the efficient inhibition of eIF2α phosphorylation and the subsequent promotion of Ad replication. Conversely, overexpression of Dicer significantly inhibits Ad replication. Transfection with mivaRNA does not affect eIF2α phosphorylation or Ad replication. These results indicate that Dicer-mediated processing of VA-RNAs leads to loss of activity of VA-RNAs for enhancement of Ad replication and that Dicer functions as a defence system against Ad in mammalian cells.